Carbon Performance and Financial Performance: How R&D Makes a Difference Pre‐ and Post‐Paris Accord - Mohamad H. Shahrour (21393698) (2024)
This study examines how R&D investments influence U.S. firms' abilities to align environmental initiatives with financial outcomes. It employs a sample of 229 firms listed on the S&P 500 between 2003 and 2021 and multivariate panel regression models with fixed effects to explore how R&D moderates the relationship between corporate carbon performance (CP) and financial performance (ROA). Findings reveal that a 1% increase in CP corresponds to a 0.429% increase in ROA. Moreover, R&D positively enhances this association, with each additional 1% R&D amplifying the CP's effect on financial performance by 0.154 units. However, following the U.S. withdrawal from the Paris Climate Agreement, the moderating effect of R&D diminishes significantly. These results are robust to alternative analyses and emphasise the importance of stable climate policies for fostering green innovation. The study emphasises the important role of R&D to sustain long‐term competitive advantage in the face of evolving environmental regulations. It further suggests that firms can benefit from prioritising R&D, fostering innovation in green technologies and adapting to environmental regulations. This alignment of sustainability with profitability provides a competitive edge, promotes long‐term environmental goals and sets industry benchmarks, ultimately driving a more sustainable business landscape. Other Information Published in: International Journal of Finance & Economics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ijfe.3109